Physical, genetic and functional interactions between the eisosome protein Pil1 and the MBOAT O-acyltransferase Gup1. Issue 1 (23rd December 2020) - Tulha, Joana; Amorim-Rodrigues, Mariana; Esquembre, Lidia Alejo; Rauch, Sebastien; Tamás, Markus J; Lucas, Cândida
ABSTRACT: The Saccharomyces cerevisiae MBOAT O -acyltransferase Gup1 is involved in many processes, including cell wall and membrane composition and integrity, and acetic acid-induced cell death. Gup1 was previously shown to interact physically with the mitochondrial membrane VDAC (Voltage-Dependent Anion Channel) protein Por1 and the ammonium transceptor Mep2. By co-immunoprecipitation, the eisosome core component Pil1 was identified as a novel physical interaction partner of Gup1. The expression of PIL1 and Pil1 protein levels were found to be unaffected by GUP1 deletion. In ∆gup1 cells, Pil1 was distributed in dots (likely representing eisosomes) in the membrane, identically to wt cells. However, ∆gup1 cells presented 50% less Pil1-GFP dots/eisosomes, suggesting that Gup1 is important for eisosome formation. The two proteins also interact genetically in the maintenance of cell wall integrity, and during arsenite and acetic acid exposure. We show that Δgup1 Δpil1 cells take up more arsenite than wt and are extremely sensitive to arsenite and to acetic acid treatments. The latter causes a severe apoptotic wt -like cell death phenotype, epistatically reverting the ∆gup1 necrotic type of death. Gup1 and Pil1 are thus physically, genetically and functionally connected. Abstract : Yeast MBOAT O -acyltransferase Gup1 interacts physically, genetically and functionally with the eisosomal Pil1, and has a role in eisosome formation and cell wall integrity, and during arsenite and acetate stress.